2019
DOI: 10.1177/0145482x18818615
|View full text |Cite
|
Sign up to set email alerts
|

Intra- and Interpersonal Factors in Adolescence Predicting Loneliness among Young Adults with Visual Impairments

Abstract: Introduction: Youths with visual impairments (i.e., blindness or low vision) experience difficulties with forming and maintaining social relationships with peers. These difficulties challenge their psychosocial functioning and put them at risk of being lonelier later in life. The study's primary goal was to investigate how intra-and interpersonal factors during adolescence influence Loneliness in young adulthood. Methods: Analyses were conducted on data from a national data set. Participants (N ¼ 96) were inte… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

1
8
0
7

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 36 publications
1
8
0
7
Order By: Relevance
“…En las interacciones existe una dificultad, cuando no una imposibilidad, para distinguir las claves visuales, como son los gestos, las expresiones faciales o el contacto ocular (Gourgey, 1999), lo que, en muchas ocasiones, supone que no se pueda reaccionar a estas claves, a lo que hay que añadir la dificultad añadida para localizar a la persona que está hablando (Van der Ham et al, 2021). Ello, además, como señalan Veerman et al, (2019), aumenta la posibilidad de mostrar un comportamiento socialmente inapropiado durante las interacciones, ya que muchas de las normas sociales solo se pueden aprender o asimilar a partir de la experiencia visual. Pero también puede llevar aparejado dificultades para predecir el comportamiento o las reacciones de los interlocutores a partir de sus expresiones faciales (Augestad, 2017).…”
Section: Introductionunclassified
“…En las interacciones existe una dificultad, cuando no una imposibilidad, para distinguir las claves visuales, como son los gestos, las expresiones faciales o el contacto ocular (Gourgey, 1999), lo que, en muchas ocasiones, supone que no se pueda reaccionar a estas claves, a lo que hay que añadir la dificultad añadida para localizar a la persona que está hablando (Van der Ham et al, 2021). Ello, además, como señalan Veerman et al, (2019), aumenta la posibilidad de mostrar un comportamiento socialmente inapropiado durante las interacciones, ya que muchas de las normas sociales solo se pueden aprender o asimilar a partir de la experiencia visual. Pero también puede llevar aparejado dificultades para predecir el comportamiento o las reacciones de los interlocutores a partir de sus expresiones faciales (Augestad, 2017).…”
Section: Introductionunclassified
“…Persons with visual impairment experience difficulties with forming and maintaining social relationships. This difficulty challenges their psychosocial functioning and results in a sense of loneliness (Veerman et al, 2019). Research from K. Yang and Victor (2011) has shown that these problems are not only experienced by older adults but also by young people with vision loss.…”
Section: Introductionmentioning
confidence: 99%
“…Persons with visual impairment experience difficulties with forming and maintaining social relationships. This difficulty challenges their psychosocial functioning and results in a sense of loneliness (Veerman et al, 2019). Research from K.…”
Section: Introductionmentioning
confidence: 99%
“…Despite these challenges, factors that can positively affect developmental processes, such as coping on family support, social environment, and children's ability to adapt, can have a positive influence on children with visual impairments [3]. One way to help visually impaired people overcome the impediments of their disability is to strengthen their adaptation to life.…”
Section: Introductionmentioning
confidence: 99%